2021
DOI: 10.3389/fmicb.2021.673784
|View full text |Cite
|
Sign up to set email alerts
|

A Patched-Like Protein PsPTL Is Not Essential for the Growth and Response to Various Stresses in Phytophthora sojae

Abstract: Patched (Ptc) and Patched-related (Ptr) proteins containing sterol-sensing domains (SSD) and Patched domains are highly conserved in eukaryotes for lipid transport and metabolism. Four proteins containing predicted SSD and Patched domains were simultaneously found by searching the Phytophthora sojae genome database, and one of them was identified as a Patched-like (PTL) protein. Here, we investigated the biological function of PsPTL. The expression level of PsPTL was higher during mycelial and sporulation stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…Therefore, it was predicted that PcSCP1, PcSCP2, and PcSCP4 are NPC1 related proteins, while PcSCP3 is a Patched-like protein. This is in agreement with the findings from a previous study analyzing the phylogeny of SCPs from P. sojae ( 18 ). Transmembrane domain prediction indicated that these four PcSCPs contain 13, 13, 10, and 13 transmembrane domains, respectively ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, it was predicted that PcSCP1, PcSCP2, and PcSCP4 are NPC1 related proteins, while PcSCP3 is a Patched-like protein. This is in agreement with the findings from a previous study analyzing the phylogeny of SCPs from P. sojae ( 18 ). Transmembrane domain prediction indicated that these four PcSCPs contain 13, 13, 10, and 13 transmembrane domains, respectively ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Knocking out of PcSCP3 individually or on the basis of double-gene knockout strain had no obvious impact on biological characteristics, indicating that this gene may not be essential for P. capsici . This is consistent with the results of another study, where the ortholog of PcSCP3 was individually knocked out in P. sojae ( 18 ). We also found some of the single-gene knockout transformants, when treated with sterol, produced fewer zoospores compared to the wild-type strain.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations